Movie Review "Island of Fear" under the eyes of Cognitive Psychology (Research, Society and Development, 2019)
The present study addressed a cinematographic analysis of the film "The Island of Fear". Through the look of Psychology, this activity comes as an attempt to construct and apprehend the programmatic content transmitted in the Basic Process discipline. The objective of this article was to present a clinical case study from the bias of Cognitive Psychology, through the analysis of the behavior of the main character of the film. Through the analysis of scenes of the film it was possible to investigate specifically how the displacements of the character are associated with the basic cognitive processes, such as memory, learning, perception, attention and language. The collection of bibliographic data was done in the electronic databases: Scielo, Pepsic, Virtual Health Library (VHL), and visits were also made to the physical library of the University. The results of the film analysis show that the patient Andrew Laeddis from the point of view of cognitive psychology presented quantitative sensory perception changes like Hyperesthesia, as well as qualitative alterations of sensoperception - hallucinations and hallucinose pictures. It was observed that the patient also presented quantitative pathological memory alterations - Amnesia or Hypnomnesia, qualitative pathological alterations of memory called mnemic illusions mnemic hallucinations. It is concluded that the case study through the film analysis made it possible to associate the behaviors of the main character of the film to Ilha do Medo to the basic cognitive processes studied theoretically in the Basic Processes discipline. This activity, even though through fiction, also enabled academics to observe the aspects, characteristics and symptoms from a Cognitive Psychology perspective of the mental disorder characterized in this study.